Penerapan ISO 45001:2018 terhadap Peningkatan Produktivitas - Anang Novida Harinurdin; Yunita Primasanti; Erna Indriastiningsih (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
According to data from the International Labor Organization (ILO), every year there are more than 2.78 million deaths and 378 million injuries due to work accidents or occupational diseases. At PT. XXX, since the site opened in 2014, there have been 16 accident cases, while in 2021 there were 9 cases recorded. OB removal production in 2014 reached 4,105,279 tons, and in 2021 it will increase to 16,942,212 tons. This research aims to analyze the relationship between implementing ISO 45001:2018 and efforts to increase productivity. The research instrument was a questionnaire with a sample of 30 people and an ISO 45001:2018 audit checklist to carry out gap analysis. The validity test using Bivariate Pearson correlation showed good validity (r > 0.5, p < 0.01), and the reliability test showed very high internal consistency with a Cronbach's Alpha value of 0.993. The gap analysis results show that most of the standard clauses have been implemented well (value > 3.00), such as leadership and commitment (3.77), participation and consultation (3.83), and hazard identification (3.25). However, determining the scope of the system needs improvement (value 2.80). The total gap analysis score reached 84%, which shows good implementation. Optimal implementation of ISO 45001:2018 has been proven to reduce accidents and injuries, which contributes to increasing productivity at PT. XXX.